Oliver Twist - Dickens, Charles, 1812-1870 (Delhi : Global Media, 2007)
An orphan, reared in a workhouse, runs away to London where he is captured by a gang of thieves. The leering Artful Dodger, the murderous Bill Sikes and the master thief Fagin are just some of the unforgettable charavters in this heart-rendering tale
Title from container
System requirements: Window 95/98/ME/2000/NT/XP/Vista ; 16 MB RAM or greater ; CD-ROM drive 4x or greater Pentium PC or higher ; 16 bit sound card ; 50 MB available HD space ; 256 colour VGA monitor or greater ; Macromedia Flash Player ; Adobe Acrobat Reader
Keywords: Orphans -- Fiction; Poor -- Fiction; Thieves -- Fiction; Kidnapping victims; London (England) -- Fiction